2017
DOI: 10.1038/s41598-017-10236-x
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Amyloids Hijack Prion Protein to Gain Cell Entry, Facilitate Cell-to-Cell Spreading and Block Prion Replication

Abstract: The precise molecular mechanism of how misfolded α-synuclein (α-Syn) accumulates and spreads in synucleinopathies is still unknown. Here, we show the role of the cellular prion protein (PrPC) in mediating the uptake and the spread of recombinant α-Syn amyloids. The in vitro data revealed that the presence of PrPC fosters the higher uptake of α-Syn amyloid fibrils, which was also confirmed in vivo in wild type (Prnp +/+) compared to PrP knock-out (Prnp −/−) mice. Additionally, the presence of α-Syn amyloids blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 44 publications
10
143
1
Order By: Relevance
“…During shedding, PrP C is released from the plasma membrane by a disintegrin and metalloproteinase (ADAM) enzyme, namely, ADAM10, in a glycosylated form without the GPI anchor and designated as “shed PrP.” Although definite functions of “shed PrP” are not known to date, the shedding process regulates the membrane levels of PrP C and thus its functions at the cell surface. Similar to α‐synuclein, recent work by Jarosz‐Griffiths et al found that the toxicity and cellular binding of Aβ oligomers can be reduced by shedding of PrP C , thereby pointing towards a contribution as a receptor in AD. Moreover, PrP C is expressed in immune cells as well, particularly on mast cells .…”
Section: Physiology Of the Prpmentioning
confidence: 99%
“…During shedding, PrP C is released from the plasma membrane by a disintegrin and metalloproteinase (ADAM) enzyme, namely, ADAM10, in a glycosylated form without the GPI anchor and designated as “shed PrP.” Although definite functions of “shed PrP” are not known to date, the shedding process regulates the membrane levels of PrP C and thus its functions at the cell surface. Similar to α‐synuclein, recent work by Jarosz‐Griffiths et al found that the toxicity and cellular binding of Aβ oligomers can be reduced by shedding of PrP C , thereby pointing towards a contribution as a receptor in AD. Moreover, PrP C is expressed in immune cells as well, particularly on mast cells .…”
Section: Physiology Of the Prpmentioning
confidence: 99%
“…Recently, different studies reported the existence of αSyn interactors that may be involved in the cell‐to‐cell transmission of αSyn pathology (Fig. ).…”
Section: Different Cell Surface Proteins Mediate the Internalization mentioning
confidence: 99%
“…More recently, PrP C was identified as a possible sensor for αSyn aggregates . In addition to interacting with αSyn and amyloid‐β (Aβ), it was recently proposed that PrP C might act as a conformation‐specific sensor for disease‐associated proteins, suggesting a more general role in the pathogenesis of various neurodegenerative diseases .…”
Section: Different Cell Surface Proteins Mediate the Internalization mentioning
confidence: 99%
See 2 more Smart Citations